Impact of ambient air pollution on physical activity among adults: a systematic review and meta-analysis - An, Ruopeng; Zhang, Sheng; Ji, Mengmeng; Guan, Chenghua (Perspectives in public health, 2018)
Aims: This study systematically reviewed literature regarding the impact of ambient air pollution on physical activity among children and adults. Methods: Keyword and reference search was conducted in PubMed and Web of Science to systematically identify articles meeting all of the following criteria – study designs: interventions or experiments, retrospective or prospective cohort studies, cross-sectional studies, and case-control studies; subjects: adults; exposures: specific air pollutants and overall air quality; outcomes: physical activity and sedentary behaviour; article types: peer-reviewed publications; and language: articles written in English. Meta-analysis was performed to estimate the pooled effect size of ambient PM2.5 air pollution on physical inactivity. Results: Seven studies met the inclusion criteria. Among them, six were conducted in the United States, and one was conducted in the United Kingdom. Six adopted a cross-sectional study design, and one used a prospective cohort design. Six had a sample size larger than 10,000. Specific air pollutants assessed included PM2.5, PM10, O3, and NOx, whereas two studies focused on overall air quality. All studies found air pollution level to be negatively associated with physical activity and positively associated with leisure-time physical inactivity. Study participants, and particularly those with respiratory disease, self-reported a reduction in outdoor activities to mitigate the detrimental impact of air pollution. Meta-analysis revealed a one unit (μg/m3) increase in ambient PM2.5 concentration to be associated with an increase in the odds of physical inactivity by 1.1% (odds ratio = 1.011; 95% confidence interval = 1.001, 1.021; p-value < .001) among US adults. Conclusions: Existing literature in general suggested that air pollution discouraged physical activity. Current literature predominantly adopted a cross-sectional design and focused on the United States. Future studies are warranted to implement a longitudinal study design and evaluate the impact of air pollution on physical activity in heavily polluted developing countries.